Institute Of Graduate Studies : Institut Pengajian Siswazah-IPSis: Graduate Programmes 2003/2004 / Institute of Graduate Studies, UiTM - UiTM, Institute of Graduate Studies (Institute of Graduate Studies, UiTM, 2003)
UiTM takes pride in its establishment as one of the premier institutions of higher education in the country. Although the history of UiTM dates back to 1956, the genesis and growth of the Institute of Graduate Studies (IGS) can be traced to April 1997.